Minería de texto histórica - colaboración al proyecto "Revealing Cooperation and Conflict Project" (2017)
The growing interest in historical documents, their analysis and the ability to share them in digital formats, has been in the eyes of both the humanities and science and specifically in computing, from some branches such as text mining, data mining or The machine learning. It is important to preserve such historical documents for both research and use in academic settings so that they are truly profitable and transcend beyond a library. For this project, entitled "Historical Text Mining, Collaboration to the Revealing Cooperation and Con fl ict Project", several problems were analyzed, including as one of the main ones, the fact that the basic research documents are written in historical language And not modern so it is difficult to implement some techniques of Text Mining. The open and participatory Revealing Cooperation and Con fl ict Project is intended to propose a work methodology based on text mining techniques in order to discover information that is not evident and relevant to the development of the research being carried out.